2015
DOI: 10.1186/s13018-015-0317-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic ossification following hip arthroplasty: a comparative radiographic study about its development with the use of three different kinds of implants

Abstract: BackgroundOur purpose was to record the incidence of heterotopic ossification (HO) following hip replacement by different variables to identify patient groups that are likely to develop HO in the absence of a prophylactic protocol.MethodsRadiographically, we studied 651 patients having undergone hip joint replacement, evaluating three kinds of implants: ceramic-ceramic-coupled total hip replacement (THR), TriboFit® with polycarbonate urethane-ceramic coupling and endoprosthesis. Each patient was analysed for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 25 publications
3
26
2
1
Order By: Relevance
“…This last finding has been also noted by Repantis et al [10]. In contrast to the present study Biz et al found a higher HO rate for the STD-Bauer approach ( p  = 0.0163) when compared to the STD-Watson-Jones [11]. These different results could be related to the different type of used implants that included also patients who underwent a hemiprothesis.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This last finding has been also noted by Repantis et al [10]. In contrast to the present study Biz et al found a higher HO rate for the STD-Bauer approach ( p  = 0.0163) when compared to the STD-Watson-Jones [11]. These different results could be related to the different type of used implants that included also patients who underwent a hemiprothesis.…”
Section: Discussioncontrasting
confidence: 49%
“…There is only scarce evidence about the influence of the surgical approach on HO occurrence. Not more than two different approaches have yet been simultaneously compared in terms of HO [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…HO development following ABMS THA surgery was 86/233, or 36.9%, which is comparable to studies of direct anterior [16] and posterior THA [17], and lower than the prevalence with a direct lateral approach with (Liverpool) [18] and without (Hardinge-Bauer) [19] bone attachment. Our results demonstrate higher rates of HO compared with two other reports of the ABMS technique [20,21], and we are unsure of the reason for these differences.…”
Section: Discussionsupporting
confidence: 62%
“…PD has been described as a pathology associated with higher rates of HO [24]. Pellegrini and Gregoritch [21] state that PD patients are at an increased risk for HO because of systemic diathesis.…”
Section: Discussionmentioning
confidence: 99%